Children's responses to a picturebook during a small group, co-constructed read-aloud : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Palmerston North, New Zealand - Braid, Christine L (Massey University, 2012)
This study investigated the responses that 21 nine and ten year old children gave to a picturebook read-aloud in small groups within their classroom. The group sessions involved a co-constructed approach based on the children's interactions with the book and each other. The research questions focused on the ways the children responded to the narrative as well as on how they built on each other's ideas to co-construct meaning. The study looked at these questions in the context of the small group and co-constructed nature of the event. The picturebook Luke’s Way of Looking by Nadia Wheatley and Matt Ottley (1999) was read aloud to each group and the responses and discussion from these sessions were recorded. The sessions produced rich data, both in quantity and quality. A framework of analysis based on and adapted from the extensive work of Lawrence Sipe (2008) allowed the data to be categorised, analysed, and discussed. The framework was adapted by considering aspects of the SOLO taxonomy (Biggs & Collis, 1982) as well as the picturebook elements that the children used for their response. The results are presented in relation to this framework. The findings revealed that the children engaged with the picturebook in ways that enhanced their literary understandings and their thinking about a book. Using the framework of analysis showed that the children's responses fitted into all the categories that Sipe (2008) established for literary understanding and in a spread that was similar to the responses from his study. The children interpreted the messages from the picturebook by using both the words and the pictures and they achieved complex levels of thought by interacting with each other and with the book. The picturebook enabled them to make inferences and draw conclusions based on how the illustrator used different elements to convey a message. In particular, the children used colour, light, and symbol to explore ideas about possible meanings in the illustrations. The small group setting enabled them to engage with the book and with each other with ease. The co-constructed approach meant children shared their ideas as they formed them and they built on each other's ideas to a complex level of thinking. The findings provide evidence that carefully selected picturebooks are an appropriate resource for nine and ten year old children. The findings also show that the small group and the co-constructed approach are important considerations for developing discussions that value the child's voice in the classroom context. These results have implications for school wide literacy policy and classroom practice.
Keywords: Children's literature; Picture books for childen; School children; Books and reading; Study and teaching; Primary